Three-dimensional printing Cu-Ni modified electrode, preparation method thereof and application of three-dimensional printing Cu-Ni modified electrode in electro-catalysis nitrate reduction

The three-dimensional printed Cu-Ni modified electrode prepared by selective laser melting technology solves the problems of reduced selectivity and increased energy consumption when treating nitrate-enriched wastewater, and achieves an efficient and stable nitrate reduction reaction, which is suitable for industrial applications.

CN119703120APending Publication Date: 2025-03-28CHINA CONSTR EIGHT ENG DIV CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411598187.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When traditional electrochemical reactors treat nitrate-enriched wastewater, selectivity is reduced, energy consumption is increased, and the membrane is susceptible to organic pollutants and dissolved solids. It has a service life of less than 200 hours, which cannot meet the stability and energy efficiency requirements of industrial applications.

Method used

Selective laser melting (SLM) technology is used to prepare three-dimensional printed Cu-Ni modified electrodes, mix copper and nickel powder by ball mill to form molded powder, and laser scanning and melting is performed through a three-dimensional printer to form a Cu-Ni electrode with a porous structure.

Benefits of technology

It achieves a NO3-removal rate, NH3 selectivity and Faraday efficiency of more than 70% at low applied voltages (-1.1~-1.4V), and the electrode has good corrosion resistance and long-term stability, which is suitable for treating real electroplating wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119703120A_ABST
    Figure CN119703120A_ABST
Patent Text Reader

Abstract

The invention provides a three-dimensional printing Cu-Ni modified electrode, a preparation method thereof and application of the three-dimensional printing Cu-Ni modified electrode in electro-catalysis nitrate reduction. The prepared three-dimensional printing Cu-Ni modified electrode is prepared through a selective laser melting (SLM) technology, the cost is greatly reduced, the forming time is short, and the three-dimensional Cu-Ni electrode with a solid area and multiple pores is suitable for being applied to an electrochemical reactor for electrocatalytic nitrate reduction; the skeleton of the electrode shows the path of the electrolyte in the porous microstructure of the electrode; when the Cu-Ni working electrode system is used for treating real electroplating wastewater, the NO3 <-> removal rate, the NH3 selectivity and the Faraday efficiency can exceed 70% when the applied voltage is-1.1 V to-1.4 V; good corrosion resistance and long-term stability are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysis, and in particular relates to a three-dimensional printed Cu-Ni modified electrode and a preparation method thereof, and application thereof in electrocatalytic nitrate reduction. Background Art

[0002] In order to reduce carbon emissions from industrial ammonia production, some studies have proposed the use of electrocatalytic nitrate reduction as an alternative to the traditional Haber-Bosch ammonia synthesis process. However, most of the global nitrate production still relies on the Ostwald process, i.e., ammonia gas oxidation. Therefore, this research path needs to be re-evaluated from the perspective of circular economy, considering nitrate-rich industrial wastewater as the main source of ammonia production. Industrial processes such as chemical synthesis, military enterprises and fertilizer production can all generate nitrate-rich wastewater. Part of this wastewater is mixed with domestic sewage. High levels of nitrate in concentrated liquids are usually classified as hazardous waste and must be evaporated and solidified before they can be landfilled. Excessive nitrate loads not only increase the cost of sewage and waste treatment, but also pose a risk of contaminating groundwater.

[0003] The electrocatalytic nitrate reduction reaction (ENRR) offers a solution to convert nitrates into ammonia, providing a sustainable approach to treat these nitrate-rich wastewaters. Recovering ammonia through ENRR could drastically reduce the cost of wastewater treatment and partially meet the global demand for ammonia, thereby reducing carbon emissions from the Haber-Bosch process.

[0004] Conventional electrochemical reactors typically use gas stripping to separate ammonia and water and a proton exchange membrane to prevent re-oxidation of ammonia at the anode. However, these systems are insufficient to treat nitrate-rich wastewaters, which contain high levels of salts, organic contaminants, dissolved solids, and alkalinity. Due to limited mass transfer in conventional reactors, ENRR selectivity decreases in the late stages of the reaction, which ultimately leads to increased energy consumption for nitrate to ammonia conversion. In addition, the membrane is susceptible to organic contaminants and dissolved solids. In this setup, the service life of conventional reactors cannot exceed 200 hours. For practical industrial applications, the reactor must demonstrate robust operational stability while facilitating energy-efficient ammonia stripping. Such a reactor requires extremely high mass transfer efficiency to achieve high nitrate to ammonia conversion performance, and the key challenges are creating a flow-through system and developing appropriately matched electrodes.

[0005] Generally, there are a variety of electrode materials that can be used in aqueous solution for the electrocatalytic reduction of nitrates, including transition metals, noble metals, and non-metals, and they are designed through morphology and size control, lattice defect construction, surface interface design, heteroatom doping, vacancy engineering, etc. Among transition metals, Cu exhibits the highest catalytic activity, can quickly achieve nitrate reduction with ammonium as the product, and exhibits the highest electrocatalytic kinetics for reducing nitrate to nitrite, various copper-based catalysts, including single-substance Cu with different morphologies (particles, nanosheets, nanoblocks, nanobelts, nanowires), Cu / oxide composite catalysts, copper-based binary alloys, etc.

[0006] To date, electrocatalytic nitrate reduction reaction (ENRR) to convert nitrate to ammonia with Faradaic efficiencies exceeding 90% have been achieved on copper-based catalysts, however, very high applied voltages (above 0.96 V in 1 M KOH electrolyte) are required to achieve Faradaic efficiencies exceeding 90%.

[0007] The method for making Cu electrocatalytic electrodes usually involves electrodeposition of Cu on PTFE film, which has good catalytic performance and improves the efficiency of catalyst preparation. However, the disadvantage is the low catalytic stability. At the same time, when the macroscopic volume of the sample is gradually expanded, the low specific surface area will become an obstacle to mass transfer, thereby affecting the efficiency of the catalyst. Summary of the invention

[0008] In view of the defects of the prior art, the object of the present invention is to provide a three-dimensional printed Cu-Ni modified electrode and a preparation method thereof and application in electrocatalytic nitrate reduction.

[0009] To achieve the above purpose, the solution adopted by the present invention is as follows:

[0010] In a first aspect, the present invention provides a method for three-dimensionally printing a Cu-Ni modified electrode, which is prepared by selective laser melting (SLM) technology, comprising the following steps:

[0011] Step (1), mixing spherical copper powder and spherical nickel powder in a ball mill to form a molding powder for three-dimensional printing;

[0012] Step (2), feeding the molding powder into a powder feeding cylinder or a powder dropping hopper of a 3D printer, and laying a layer of molding powder on a molding substrate by a powder laying device;

[0013] Step (3), performing laser selective scanning on the laid molding powder, melting the molding powder and solidifying and sintering to form a molding layer;

[0014] Step (4), after completing the scanning of one molding layer, the molding substrate is lowered by a layer thickness, and then a new layer of molding powder is continuously laid on the molding layer, and the new layer of molding powder is selectively scanned by laser;

[0015] Step (5), repeating step (4) until a three-dimensionally printed Cu-Ni modified electrode having a structure consisting of a Cu solid solution and a Ni reinforcement phase and having multiple pores is printed on the molded substrate.

[0016] Preferably, in step (1), ball milling is carried out under argon protection, the ball milling speed is 100-300 rpm, the ball milling time is 1-3 h, the particle sizes of the spherical copper powder and the spherical nickel powder are both 15-53 μm, and the mass ratio of the spherical copper powder to the spherical nickel powder is (5-10):1.

[0017] Preferably, in the molding powder, the mass percentage of copper is 80%-90%, and the mass percentage of nickel is 10%-20%; the powder particle size of the molding powder is 5-35 μm, the sphericity is ≥0.85, and the bulk density is ≥6.5 g / cm 3 , tap density ≥8.0g / cm 3 , fluidity ≤20s / 50g.

[0018] Preferably, in step (2), step (4) and step (5), the thickness of each layer of molding powder laid by the powder laying device is 30 μm.

[0019] Preferably, in step (3), step (4) and step (5), a yttrium rubidium fiber laser with a focal diameter of 100 μm is used for laser scanning, a linear scanning method is adopted, the laser power is 100-300 w, the laser scanning speed is 800-1200 mm / s, the laser scanning spacing is 0.05-0.12 mm, and the rotation angle of layer-by-layer scanning is 0-90°.

[0020] Preferably, during the entire three-dimensional printing process, the cavity is filled with an inert gas, wherein the inert gas is selected from one or both of argon and nitrogen.

[0021] In a second aspect, the present invention also provides a three-dimensional printed Cu-Ni modified electrode prepared by the preparation method as described above, wherein the microstructure of the three-dimensional printed Cu-Ni modified electrode consists of a Cu metal solid solution and a Ni metal glass strengthening phase.

[0022] Preferably, the porosity of the 3D printed Cu-Ni modified electrode is 60%-80% and the resistivity is 4×10 -5 -5×10 -5 Ωcm.

[0023] In a third aspect, the present invention also provides a use of the three-dimensional printed Cu-Ni modified electrode as described above in electrocatalytic nitrate reduction.

[0024] Preferably, the three-dimensional printed Cu-Ni modified electrode is used as the working electrode, the platinum electrode is used as the counter electrode, and the Ag / AgCl electrode is used as the reference electrode to form a three-electrode system; the three-electrode system is placed in a nitrate-containing double-chamber electrolytic cell to perform an electrocatalytic reaction of converting nitrate into high-value-added ammonia; wherein the nitrate concentration in the nitrate-containing water body is 10-300 mg N / L, and Na 2 SO 4 The concentration of the electrolyte is 0.06-0.2 mol / L, and the denitrification time is 1-3h. When the applied voltage is -1.1~-1.4V, NO 3 - Removal rate, NH 3 The selectivity and Faradaic efficiency are both over 70%.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The three-dimensional printed Cu-Ni modified electrode prepared by the present invention is prepared by selective laser melting (SLM) technology, which greatly reduces the cost and shortens the molding time. The three-dimensional Cu-Ni electrode with solid area and multiple pores is suitable for the application of electrochemical reactor flowing through electrocatalytic nitrate reduction. The skeleton of the electrode shows the path of the electrolyte in the porous microstructure of the electrode. When the constructed Cu-Ni working electrode system treats real electroplating wastewater, NO 3 - Removal rate, NH 3 The selectivity and Faraday efficiency can exceed 70% when the applied voltage is -1.1 to -1.4V; it has good corrosion resistance and long-term stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic structural diagram of the selective laser melting three-dimensional printing device involved in the present invention.

[0028] Figure 2 This is a transmission electron microscope image of the three-dimensional printed Cu-Ni modified electrode involved in the present invention.

[0029] Figure 3 This is a cyclic stability chart of the ammonia selectivity and Faraday efficiency of the three-dimensional printed Cu-Ni modified electrode in Example 1 of the present invention.

[0030] Figure 4 This is a chart of nitrate removal rate, ammonia selectivity and Faraday efficiency of the three-dimensionally printed Cu-Ni modified electrode, Cu electrode and Ni electrode in Example 3 of the present invention.

[0031] Figure 5 This is a graph of nitrate removal rate, ammonia selectivity and Faraday efficiency of the three-dimensionally printed Cu-Ni modified electrode at a voltage of -0.9 to -1.4 V in Example 4 of the present invention. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific implementation methods.

[0033] The present invention provides a method for three-dimensional printing of Cu-Ni modified electrodes, which is prepared by selective laser melting (SLM) technology. Selective laser melting (SLM) is a technology that uses the heat of a laser beam to completely melt the printing material (metal, ceramic), and forms a product after cooling and solidification. Since the powder material is in a completely molten state during the manufacturing process, it has a higher density than selective laser sintering (SLS).

[0034] The method for three-dimensional printing of Cu-Ni modified electrodes provided by the present invention is implemented by a selective laser melting three-dimensional printing system, which includes: a computer system for molding control and a selective laser melting three-dimensional printing device.

[0035] During the preparation process, first, in a computer system used for molding control, a CAD model of the formed part is established according to the shape of the 3D printed Cu-Ni modified electrode formed part to be processed, and it is drawn using, for example, Magics 3D design software. Then, it is layered and sliced ​​in the height direction to divide it into slices of uniform thickness. The contour information of the 3D formed part is converted into 2D contour information, and a slice file is generated. The slice file includes the cross-sectional contour information and processing path of the formed part. Subsequently, the slice file is imported into a selective laser melting 3D printing device.

[0036] In the present invention, Figure 1As shown, the selective laser melting 3D printing device 1 used includes a molding studio 10, a molding substrate 20, a powder spreading device 30, a powder feeding cylinder or a powder dropping hopper 40 and a laser device 50. Among them, the molding studio 10 is a closed sealed chamber, which is vacuum or filled with a predetermined concentration of inert gas, and the oxygen concentration therein is controlled to be less than 100ppm to avoid oxidation damage to metal powder or molded parts. The molding substrate 20 and the powder spreading device 30 are both arranged in the molding studio 10, horizontally arranged, usually a square or round stainless steel plate, and the powder spreading device 30 is used to spread a predetermined thickness of molding powder on the molding substrate 20. The molding powder laid on the molding substrate 20 passes through the laser beam of the laser device 50 according to the specified scanning path to melt and deposit metal or alloy powder layer by layer, and accumulate to form a three-dimensional entity with a density higher than 95%.

[0037] Based on the above selective laser melting 3D printing device, combined with Figure 1 The present invention provides a method for three-dimensional printing of Cu-Ni modified electrodes, comprising the following steps:

[0038] Step (1), mixing spherical copper powder and spherical nickel powder in a ball mill to form a molding powder for three-dimensional printing;

[0039] In this step, the present invention uses a composite material of Cu and Ni as an electrocatalytic electrode. It is confirmed by the embodiments of the present invention that the use of a Cu-Ni alloy material as an electrocatalytic electrode can effectively solve the problem that a single Cu-based electrode requires a very high applied voltage to achieve a high Faraday efficiency in the electrocatalytic nitrate reduction reaction (ENRR). At the same time, compared with a single Cu-based electrode or a single Ni-based electrode, the Cu-Ni alloy material can exhibit higher electrocatalytic activity and better selectivity for a single product. The mechanism may be that Cu exhibits a high electrocatalytic activity for NO 3 *, and Ni is the connection point of H*. Therefore, replacing some Cu atoms with Ni atoms can reduce the generation of NH 3 The density of active sites can regulate the absorption energy and promote NH 3 desorption, thereby improving the catalytic activity.

[0040] In this step, high-purity copper powder and high-purity nickel powder can be prepared in advance by water mist method or gas atomization method to obtain pure amorphous powder. After the powder is dried, it is sieved with, for example, a 450-mesh sieve to obtain spherical copper powder or spherical nickel powder with a particle size of 20-80 μm, preferably spherical copper powder or spherical nickel powder with a particle size of 15-53 μm (average particle size of 35 μm).

[0041] Then, the spherical copper powder and the spherical nickel powder are mixed in a mass ratio of (5-10): 1, and then placed in an agate pot for ball milling at a ball milling speed of 100-300 rpm for 1-3 hours. The ball milling process is preferably carried out under argon protection. After drying, a molding powder is obtained. In the molding powder, the mass percentage of copper is 80%-90%, the mass percentage of nickel is 10%-20%, the powder particle size of the molding powder is 5-35 μm, the sphericity is ≥0.85, and the loose density is ≥6.5 g / cm 3 , tap density ≥8.0g / cm 3 , fluidity ≤20s / 50g.

[0042] Step (2), in a forming control computer system, according to the shape of the three-dimensional printed Cu-Ni modified electrode formed part to be processed, a CAD model of the formed part is established, and it is drawn using, for example, Magics three-dimensional design software, and then it is sliced ​​in layers in the height direction to be divided into slices with uniform thickness, and a slice file is generated, the slice file including the cross-sectional profile information and the processing path of the formed part, and then the slice file is imported into a selective laser melting three-dimensional printing device;

[0043] Step (3), in the selective laser melting 3D printing device, 316L stainless steel of a certain size and surface finish is selected as the molding substrate 20 and fixed on a liftable workbench of the molding studio 10, and the molding substrate 20 is leveled;

[0044] In this step, other materials such as 304 stainless steel, metal alloy materials, etc. may also be selected as the molding substrate 20 .

[0045] Step (4), sealing the molding studio 10 into a sealed chamber, evacuating the chamber and then filling it with an inert gas such as argon and / or nitrogen for atmosphere protection;

[0046] In this step, the oxygen concentration in the molding studio 10 is controlled to be less than 100 ppm to avoid oxidation damage to the metal powder or the molded part. In the molded part formed subsequently, the presence of oxides will significantly affect the electrocatalytic performance of the Cu-Ni alloy electrode.

[0047] Step (5), feeding the three-dimensionally printed molding powder obtained in step (1) into a powder feeding cylinder or a powder dropping hopper 40, and laying a layer of molding powder with a thickness of preferably 30 μm on the molding substrate 20 through a powder laying device 30;

[0048] Step (6), laser processing: according to the input cross-sectional profile information of the formed part and the processing path, the forming powder on the forming substrate 20 is selectively scanned and preheated by the laser beam of the laser device 50, so that the forming powder is melted and solidified and sintered to form a forming layer;

[0049] Step (7), after completing the scanning of one molding layer, the molding substrate 20 is lowered by a layer thickness, and then a new layer of molding powder is laid on the previous molding layer, and the new layer of molding powder is selectively scanned by the laser beam of the laser device 50;

[0050] Step (8), repeat the above step (7) until a Cu-Ni modified electrode formed part is printed on the molding substrate 20.

[0051] In the above steps (6), (7) and (8), the thickness of each layer of molding powder laid by the powder laying device 30 is preferably 30 μm.

[0052] In the above steps (6), (7) and (8), the laser beam of the laser device 50 is scanned in a linear manner, and the laser power, laser scanning speed and laser scanning spacing used in each layer of laser scanning can be the same or different, for example, the laser power, laser scanning speed and laser scanning spacing can be increased or decreased layer by layer. The layer by layer can also be scanned at a certain rotation angle, for example, the layer by layer rotation angle is 90°, that is, the nth layer is scanned in a linear manner at 0 degrees, and the n+1th layer is scanned in a linear manner at 90 degrees.

[0053] In the above steps (6), (7) and (8), the laser beam of the laser device 50 uses a yttrium rubidium fiber laser with a focal diameter of 100 μm for laser scanning. The yttrium rubidium fiber laser is characterized by an output wavelength of about 1064 nanometers, and has the advantages of high efficiency, stability and reliability. It can effectively solve the problem of low effective utilization rate of laser energy in the three-dimensional printing process of Cu, so that the three-dimensional printing of Cu-Ni alloy electrodes with porous structures can be easily completed within a dozen minutes.

[0054] In the above steps (6), (7) and (8), during the laser printing process, the laser power used is preferably 100-300w, the laser scanning speed is preferably 800-1200mm / s, and the laser scanning spacing is preferably 0.05-0.12mm. Too high or too low laser power will cause micro cracks to appear on the solidified melt channel. This is because when the laser power is too high, the thermal stress is large, and the solidified melt channel cracks under the stress. When the laser power is too low, the powder is not sintered completely, which reduces the strength of the solidified melt channel and is also prone to cracking.

[0055] According to the method of the present invention, the SLM technology is utilized and the CAD model is directly completed in one step, so that the components can be easily manufactured within a dozen minutes, the cost of manufacturing the Cu-Ni alloy electrode is greatly reduced, the dimensional error is small, and the material waste can be minimized.

[0056] According to the method of the present invention, the SLM process is protected by an inert atmosphere throughout, which has a protective effect on the Cu-Ni alloy in a high temperature state, effectively avoids oxidation of the alloy, and improves the comprehensive performance of the Cu-Ni alloy electrode.

[0057] According to the method of the present invention, a three-dimensional printed Cu-Ni amorphous (metallic glass) modified electrode material with a structure consisting of a Cu metal solid solution and a Ni strengthening phase can be prepared. The obtained three-dimensional printed Cu-Ni modified electrode has a porosity of 60%-80% and a resistivity of 4×10 -5 -5×10 -5 Ωcm.

[0058] The present invention also provides an application of a three-dimensional printed Cu-Ni modified electrode prepared by the method as described above in electrocatalytic nitrate reduction.

[0059] The three-dimensional printed Cu-Ni modified electrode prepared by the method of the present invention is proved to be suitable for the application of the reactor flowing through the electrocatalytic nitrate reduction. The skeleton of the electrode shows the path of the electrolyte in the porous microstructure of the electrode, and the resistivity is of the same order of magnitude as the original Cu, which is of great significance for reducing the industrial working current density to more than hundreds of A·m -2 Severe Joule heating is very beneficial.

[0060] At the same time, the present invention also provides an electrochemical system for electrocatalytic nitrate reduction, in which the three-dimensional printed Cu-Ni modified electrode is used as a working electrode, a platinum electrode is used as a counter electrode, and an Ag / AgCl electrode is used as a reference electrode to form a three-electrode system; the three-electrode system is placed in a double-chamber electrolytic cell containing nitrate to carry out an electrocatalytic reaction of converting nitrate into high-value-added ammonia.

[0061] In the electrochemical system for electrocatalytic nitrate reduction provided by the present invention, the nitrate concentration in the nitrate-containing water is 10-300 mg N / L, Na 2 SO 4 The concentration of the electrolyte is 0.06-0.2 mol / L, and the denitrification time is 1-3h.

[0062] The embodiments of the present invention confirm that the electrochemical system for electrocatalytic nitrate reduction using the three-dimensional printed Cu-Ni modified electrode of the present invention can achieve NO 3 - Removal rate, NH 3 Both selectivity and Faradaic efficiency can exceed 70%.

[0063] The electrochemical system for electrocatalytic nitrate reduction provided by the present invention is a membrane-free electrochemical system that can realize electrochemical nitrate conversion and synchronous ammonia recovery. The electrochemical system can synchronize nitrate reduction with ammonia recovery to treat real nitrate-rich wastewater. The key components of the electrochemical system are the Cu-Ni working electrode modified with three-dimensional printed metallic glass of the present invention, which has good corrosion resistance, and a UV-assisted stripping unit. It has been confirmed by the embodiments of the present invention that when treating real electroplating wastewater, the Cu-Ni working electrode system converts more than 70% of nitrate into high-purity ammonium chloride; long-term stability tests have proved the robustness of the Cu-Ni working electrode system in treating real wastewater. In addition, technical and economic analysis and life cycle analysis have confirmed the economic feasibility and environmental benefits of the electrochemical system. Therefore, the electrochemical system for electrocatalytic nitrate reduction provided by the present invention has advanced the electrocatalytic nitric acid reduction process by one step, promoting environmental protection and the circulation of nitrogen flows in human activities.

[0064] The present invention is further described below in conjunction with examples, the purpose of which is to better understand the content of the present invention and reflect the essential characteristics of the present invention, so the examples cited should not be regarded as limiting the scope of protection of the present invention. It is also particularly pointed out here that the specific experimental methods and equipment involved in the examples are conventional methods or implemented under the conditions recommended by the manufacturer's instructions unless otherwise specified, and the reagents involved are commercially available unless otherwise specified.

[0065] Embodiment 1:

[0066] A method for three-dimensional printing of Cu-Ni modified electrodes comprises the following steps:

[0067] Step S1: The Cu-Ni electrode is Figure 1 The selective laser melting 3D printing device 1 shown is prepared by selective laser melting (SLM) technology. Magics software is used for modeling, the powder layer thickness is 30 μm, the laser power is set to 200 W, and the scanning speed is 1000 mm / s.

[0068] Step S2: the spherical copper powder and the spherical nickel powder are ball-milled and mixed in a ball mill at a ball-milling speed of 150 rpm for 2 hours so that the powders are evenly mixed, and then three-dimensional printing is performed;

[0069] Step S3: During the printing process, the 3D printing instrument is filled with argon gas to obtain a 3D printed Cu-Ni modified electrode.

[0070] Transmission electron microscopy images of 3D printed Cu-Ni modified electrodes Figure 2 shown.

[0071] A three-dimensional printed Cu-Ni modified electrode is used as a working electrode, a platinum electrode is used as a counter electrode, and an Ag / AgCl electrode is used as a reference electrode to form a three-electrode system; the three-electrode system is placed in a nitrate-containing double-chamber electrolytic cell to perform an electrocatalytic reaction of converting nitrate into high-value-added ammonia. The nitrate concentration in the nitrate-containing water is 200 mg N / L; Na 2 SO 4 The concentration of the electrolyte was 0.1 mol / L; the applied voltage was -1.3 V, and the denitrification time was 2 h.

[0072] Cyclic stability of 3D printed Cu-Ni modified electrodes for ammonia selectivity and Faradaic efficiency Figure 3 shown.

[0073] Embodiment 2:

[0074] The preparation of the electrode material and the method for catalytic reduction of nitrate are the same as those in Example 1, except that a metal Cu powder is used in the preparation of the electrode material.

[0075] Embodiment 3:

[0076] The preparation of the electrode material and the method for catalytic reduction of nitrate are the same as those in Example 1, except that a metal Ni powder is used in the preparation of the electrode material.

[0077] from Figure 4 It can be seen that the three-dimensional printed Cu-Ni modified electrode obtained in Example 1 has higher nitrate removal rate, ammonia selectivity and Faraday efficiency than the three-dimensional printed Cu electrode obtained in Example 2 and the three-dimensional printed Ni electrode obtained in Example 3.

[0078] Embodiment 4:

[0079] The preparation of the three-dimensional printed Cu-Ni modified electrode and the method for catalytic reduction of nitrate are as in Example 1, except that when performing ENRR, the voltage is selected from -0.9 to -1.4V.

[0080] from Figure 5 It can be seen that the nitrate removal rate, ammonia selectivity and Faraday efficiency of the obtained 3D printed Cu-Ni modified electrode change when the voltage changes from -0.9 to -1.4V. It can be seen that the present invention uses Cu-Ni alloy material as the electrocatalytic electrode, which can achieve NO removal when the applied voltage is -1.1 to -1.4V. 3 - Removal rate, NH 3 The selectivity and Faradaic efficiency can exceed 70%, which can effectively solve the problem that a single Cu-based electrode requires a very high applied voltage to achieve a high Faradaic efficiency in the electrocatalytic nitrate reduction reaction (ENRR).

[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for three-dimensional printing of Cu-Ni modified electrodes, characterized in that: The selective laser melting (SLM) technique includes the following steps: Step (1), mixing spherical copper powder and spherical nickel powder in a ball mill to form a molding powder for three-dimensional printing; Step (2), feeding the molding powder into a powder feeding cylinder or a powder dropping hopper of a 3D printer, and laying a layer of molding powder on a molding substrate by a powder laying device; Step (3), performing laser selective scanning on the laid molding powder, melting the molding powder and solidifying and sintering to form a molding layer; Step (4), after completing the scanning of one molding layer, the molding substrate is lowered by a layer thickness, and then a new layer of molding powder is continuously laid on the molding layer, and the new layer of molding powder is selectively scanned by laser; Step (5), repeating step (4) until a three-dimensionally printed Cu-Ni modified electrode having a structure consisting of a Cu solid solution and a Ni reinforcement phase and having multiple pores is printed on the molded substrate.

2. The method according to claim 1, characterized in that In step (1), ball milling is performed under argon protection, the ball milling speed is 100-300 rpm, the ball milling time is 1-3 h, the particle sizes of the spherical copper powder and the spherical nickel powder are both 15-53 μm, and the mass ratio of the spherical copper powder to the spherical nickel powder is (5-10):

1.

3. The method according to claim 1, characterized in that: The mass percentage of copper in the molding powder is 80%-90%, and the mass percentage of nickel is 10%-20%. The particle size of the molding powder is 5-35 μm, the sphericity is ≥0.85, and the bulk density is ≥6.5 g / cm 3 , tap density ≥8.0g / cm 3 , fluidity ≤20s / 50g.

4. The method according to claim 1, characterized in that: In step (2), step (4) and step (5), the thickness of each layer of molding powder laid by the powder laying device is 30 μm.

5. The method according to claim 1, characterized in that In step (3), step (4) and step (5), a yttrium rubidium fiber laser with a focal diameter of 100 μm is used for laser scanning, a linear scanning method is adopted, the laser power is 100-300 w, the laser scanning speed is 800-1200 mm / s, the laser scanning spacing is 0.05-0.12 mm, and the rotation angle of layer-by-layer scanning is 0-90°.

6. The method according to claim 1, characterized in that During the entire process of three-dimensional printing, the cavity is filled with an inert gas, and the inert gas is selected from one or both of argon and nitrogen.

7. A three-dimensional printed Cu-Ni modified electrode prepared by the method according to any one of claims 1 to 6, characterized in that: The microstructure of the three-dimensionally printed Cu-Ni modified electrode consists of a Cu metal solid solution and a Ni metal glass reinforcement phase.

8. The three-dimensional printed Cu-Ni modified electrode according to claim 7, characterized in that: The porosity of the 3D printed Cu-Ni modified electrode is 60%-80% and the resistivity is 4×10 -5 -5×10 -5 Ωcm.

9. Use of the three-dimensional printed Cu-Ni modified electrode as claimed in claim 7 or 8 in electrocatalytic nitrate reduction.

10. The use according to claim 9, characterized in that: The three-dimensional printed Cu-Ni modified electrode is used as the working electrode, the platinum electrode is used as the counter electrode, and the Ag / AgCl electrode is used as the reference electrode to form a three-electrode system; the three-electrode system is placed in a double-chamber electrolytic cell containing nitrate to perform an electrocatalytic reaction of converting nitrate into high-value-added ammonia; wherein the nitrate concentration in the nitrate-containing water body is 10-300 mg N / L, the concentration of the Na2SO4 electrolyte is 0.06-0.2 mol / L, and the denitrification time is 1-3 h; when the applied voltage is -1.1 to -1.4 V, NO3 - The removal rate, NH3 selectivity and Faradaic efficiency all exceeded 70%.